Research on airborne electronic hardware circuit board level certification strategy - LIU Runzhou; ZHU Hongli; MA Limin (Hangkong gongcheng jinzhan)
This article is to address the ambiguity in the current domestic certification practice based on the DO-254 Airborne Electronic Hardware Development Assurance Guidelines regarding the circuit board level certification strategy and objectives for circuit boards. By comparing and analyzing the relevant objectives for circuit board level in Advisory Circular AC 20-152A and Memorandum CM-SWCEH-001 regarding DO-254，and combining the certification concept of foreign airworthiness authorities and the current domestic industrial circumstance，this paper proposes the idea and method of using Advisory Circular AC 20-152A as a supporting material for DO-254 to be applied in the domestic airborne electronic hardware circuit board level certification practice. Meanwhile a feasibility analysis is conducted on the circuit board level requirements in Advisory Circular AC 20-152A，and based on the intent of the clause，it is optimized to adapt to the current domestic approval status. The applicability and superiority of this approach and method are demonstrated through actual project approval cases. Results show that the idea and method proposed in this paper can provide reference and inspiration for the circuit board level airworthiness compliance of domestic airborne electronic hardware.